2012
DOI: 10.1161/strokeaha.112.669622
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Carotid Endarterectomy Practice Patterns Within a Metropolitan Area

Abstract: Background and Purpose-Previous clinical studies have suggested that patients with carotid stenosis with high surgical risk features may fare better with carotid artery stenting or aggressive medical therapy. The extent to which carotid endarterectomy is still being performed in this group of patients is unclear. Methods-A retrospective audit was performed among 4 hospitals over a 2-year period. The proportion of high surgical risk patients was compared and the in-hospital stroke, myocardial infarction, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…A recent study found significant heterogeneity in the treatment of "high surgical risk" patients, with a substantial proportion still receiving CEA. [58] There have been numerous single center case series and registry publications reporting results of CAS. In industry sponsored registries, the 30 day combined risk of stroke, death and MI has varied from 3.8% to 8.6%.…”
Section: The Risks Associated With Carotid Endarterectomymentioning
confidence: 99%
“…A recent study found significant heterogeneity in the treatment of "high surgical risk" patients, with a substantial proportion still receiving CEA. [58] There have been numerous single center case series and registry publications reporting results of CAS. In industry sponsored registries, the 30 day combined risk of stroke, death and MI has varied from 3.8% to 8.6%.…”
Section: The Risks Associated With Carotid Endarterectomymentioning
confidence: 99%
“…There is a great degree of variability of this procedure across the country and even among providers in the same center. 20,21 Traditional endarterectomy employs a longitudinal arteriotomy, while eversion endarterectomy employs a transverse arteriotomy with reimplantation of the carotid artery. 22 A Cochrane review of five randomized controlled trials showed no statistically significant difference in the rates of perioperative stroke or death when comparing eversion and conventional endarterectomy with either patch angioplasty or primary closure.…”
Section: Surgical Considerationsmentioning
confidence: 99%